PENGURUSAN DAN PENGENDALIAN SURAT SUB BAGIAN UMUM DI DINAS TENAGA KERJA DAN TRANSMIGRASI DAERAH ISTIMEWA YOGYAKARTA - , NOVA KURNIASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The final report describes the mail handling of Sub Bagian Umum at the Dinas Tenaga Kerja dan Transmigrasi DIY using two systems. The system of mail handling use in manual and computerized system which aims to accelerate the mail handling process. The method of collecting data is used four stages. First, observation participation how which is used to know the mine distribution at central file. Second, method was direct interview offis in this institution. Third, literature with appropriate reference to the themes, example reference of classification system. Fourth, documentation method by recorded with photography. The main conclusion of this task is the implementation of mail handling system at the Dinas Tenaga Kerja dan Transmigrasi DIY is good arrangement. But there are making up arrange Kartu Kendali and Lembar Disposisi still difficult so must be arranged.